Spiritualization of Child Education in the Qur'anic Sufism Perspective in the Covid-19 Era - Muh. Mustakim; Kana Safrina Rouzi; Tumin Tumin (Universitas Muhammadiyah Yogyakarta, 2021)
The COVID-19 pandemic has implications for changing the attitudes and behavior of the world community, including in the field of education. The Indonesian government, in this case, has decided to study from home (BDR) for schools to universities in addition to the work from home (WFH) policy. BDR challenges have both advantages and disadvantages. Among the weaknesses that need to be watched out for is the burnout of children in online learning from home, which cannot be denied because similar conditions are also experienced by parents, which erode the enthusiasm for learning to spirituality in the family. Therefore, this paper examines how to reconstruct the spiritualization of education for children in families amid COVID-19. This qualitative research used a descriptive approach, describing the data obtained from the interpretation of the term